Networking Simulation for Intelligent Transportation Systems - Hilt, Benoit; Berbineau, Marion; Vinel, Alexey; Pirovano, Alain (Wiley-ISTE, 2017)
This book studies the simulation of wireless networking in the domain of Intelligent Transportation Systems (ITS) involving aircraft, railway and vehicular communication. On this subject, particular focus is placed on effective communication channels, mobility modeling, multi-technology simulation and global ITS simulation frameworks. Networking Simulation for Intelligent Transportation Systems addresses the mixing of IEEE802.11p and LTE into a dedicated simulation environment as well as the links between ITS and IoT; aeronautical mobility and VHD Data Link (VDL) simulation; virtual co-simulation for railway communication and control-command; realistic channel simulation, mobility modeling and autonomic simulation for VANET and quality metrics for VANET. The authors intend for this book to be as useful as possible to the reader as they provide examples of methods and tools for running realistic and reliable simulations in the domain of communications for ITS.